Evaluation of Jumputan Fabric Craftswomen’s Work Posture at Kelurahan Tahunan, Yogyakarta using Nordic Body Map Questionnaire and REBA - Maria Gratiana Dian Jatiningsih; Cici Finansia; Mahdiya Nayla (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: Kelurahan Tahunan, Umbulharjo, Yogyakarta is known as the production center of jumputan fabrics. The making process of jumputan fabrics is done manually using simple tools. This causes the craftswomen to work with non-ergonomic posture. The health impact that arises due to non-ergonomic work posture is musculoskeletal disorder. Objectives: This research is conducted to evaluate the work posture of jumputan fabric craftswoman. Research Methods: Data were obtained by filling out the Nordic Body Map (NBM) questionnaire, measuring, and observing using the Rapid Entire Body Assessment (REBA). Results: It is known that the REBA’s score of jumputan fabrics craftswomen is 9 which means high risk. Conclusion: The working posture of jumputan fabric craftswomen is high risk and needs to be changed. To overcome this, a tool can be made in the form of a table with a drain so that the craftsmen can work with a better posture.